The river - Paulsen, Gary (Delacorte Press, 1991)
Because of his success surviving alone in the wilderness for fifty-four days, fifteen-year-old Brian, profoundly changed by his time in the wild, is asked to undergo a similar experience to help scientists learn more about the psychology of survival.